PERAN PEMBINA ASRAMA DALAM MENANAMKAN NILAI-NILAI RELIGIUS PADA PESERTA DIDIK PROGRAM KEAGAMAAN - Haris Supratno; Siti Luthfiyah (Wahana Islamika: Jurnal Studi Keislaman, 2023)
This research uses a qualitative approach, while the type is field research. The object of this research is focused on the caregivers, coaches, and students in the dormitory with the aim of knowing how the role of the supervisor of the hostel in instilling religious values ​​into students in the dormitory of MAN Religious Program Denanyar Jombang. The researcher collects data through interviews, observation, and documentation methods with descriptive analysis techniques. The findings in this study indicate that the role of the hostel supervisor in instilling the religious values ​​of students is as a facilitator, educator, motivator, counselor, and figure center. The religious values ​​instilled in the MAN Religious Program dormitory include the values ​​of worship, morals, discipline and exemplary. Instilling religious values ​​in the MAN dormitory for the Denanyar Jombang Religious Program using exemplary, habituation, functional, coaching and punishment and reward methods. The inculcation of religious values ​​is one of the foundations for shaping the character of students. Religious values ​​are reflected and illustrated by students through speech, behavior, actions, and thinking in accordance with Islamic teachings, carrying out His commands and staying away from His prohibitions, promoting tolerance and creating a harmonious life. The role of the Religious Program MAN dormitory supervisor is very important to make students intellectually and morally qualified.